Heterogeneity of Ecosystem Service Interactions Through Scale Effects and Time Effects and Their Social-Ecological Determinants in the Tuo River Basin - Simin He; Yusong Xie; Jing Zhang; Yanyun Luo; Qianna Wang (Land)
Ecosystem services (ESs) assessment plays a significant role in managing ecological resources. Uncovering the complex interdependencies between ESs and their key drivers is an essential preliminary step toward the coordinated management of ESs. Currently, a major challenge lies in precisely evaluating trade-offs and synergies among ESs across different spatial and temporal scales, particularly in capturing their dynamic evolution and determinants. This study focuses on the Tuo River Basin in China, quantifying four key ESs, namely, habitat quality (HQ), nitrogen export (NE), soil conservation (SC), and water yield (WY), and assessing their interactions from 2000 to 2020 at both grid and county scales. Moreover, this study explored the social-ecological driving factors influencing these ESs. The results showed that (1) SC and WY in the region exhibited an increasing trend, HQ and NE declined, and ESs at the county scale showed a central collapse feature; (2) synergies between HQ–NE, HQ–WY, and SC–WY pairs generally increased, the relationships between NE–SC and NE–WY pairs showed slight fluctuations, and there was a decline in the synergies within the HQ–SC pair; and (3) the interplay of all drivers positively affected ESs, with land use/land cover being the most significant and GDP exerting a lower influence. ES assessment results exhibited distinctive characteristics at two scales. Based on these findings, management strategies that incorporate both scales and cross policy boundaries are proposed to effectively meet management objectives. These results can facilitate improved synergy between regional ecological protection and economic development.